Innovation in Cybersecurity: Pioneering the Future of Digital Safety - Mhatre, Rajshree Lahoo; Momin, Rizwana; Dhaygude, Mahesh; Garje, Vivek (International Journal of Engineering and Management Research, 2025)
Cybersecurity has surfaced as one of the most critical enterprises as the world becomes decreasingly connected. Digital pitfalls similar as hacking, ransomware, and data breaches are growing alarmingly, putting individualities, businesses, and governments at threat. Traditional cybersecurity styles no longer give sufficient protection. New technologies and strategies are being developed, leading to significant inventions in the field. This paper explores these inventions, fastening on technologies like Artificial Intelligence (AI), machine literacy (ML), blockchain, and Zero Trust security models. It also highlights the significance of collaboration between different sectors in driving these advancements. By assaying the current state and unborn directions of cybersecurity invention, this paper emphasizes the need for non-stop development and adaption to ensure the safety of digital means and systems.